KESIAPAN PUSKESMAS 1 NEGARA DALAM MENANGGULANGI PENINGKATAN KEJADIAN KASUS HIV/AIDS DI KABUPATEN JEMBRANA BALI 2014 - I Made Angga Prastiya (E-Jurnal Medika Udayana, 2016)
MEASURING THE PREPAREDNESS OF PUSKESMAS 1 NEGARA IN OVERCOMING THE INCREASE OF HIV/AIDS CASE IN JEMBRANA REGENCY BALI 2014 Background: Bali was ranked fifth among all provinces in Indonesia for the highest number of HIV infection and AIDS. HIV care service is available in “puskesmas” as a primary healthcare unit. There was a significant increase of HIV/AIDS cases within the working area of Puskesmas 1 Negara since the implementation of VCT service in 2013. Objective: To identify the preparedness of Puskesmas 1 Negara regarding the increase HIV/AIDS cases which began to arise since the implementation of VCT service in Puskesmas 1 Negara. Methods: This study is a descriptive qualitative study which was conducted on March 2014. Sample was collected by a non random method, which was purposive sampling. The sample in this study was chosen from parties involved in the HIV/AIDS countermeasure program in the working area of Puskesmas 1 Negara. The data was collected from interview with respondent. Thereafter will be coded, and thematic analysis was performed. Result: Based on the interview from six informant, some factors had been noted to support the preparedness of Puskesmas 1 Negara such as (1)infrastructure, (2)human resource, and (3)financial. On the other hand there were also factors that deter the preparedness of puskesmas 1 Negara such as (1)infrastructure, (2)human resource, and (3)socialization of VCT services. Conclusion: The preparedness of Puskesmas 1 Negara in providing VCT services is sufficient which is supported by adequate overall human resource and infrastructure in term of quality and quantity, however the absence of exclusive counseling room, lack of laboratorium and pharmacy personel, and minimal socialization of VCT services remain being obstacles in the implementation of VCT services. These matter had been handled by utilizing other alternative at hand.